Preferential mode of zinc and adherence to treatment: zinc syrup or zinc tablet - Singh, Om Prakash; Dutta, Abhik; Sharma, Sudeep (International Journal Of Community Medicine And Public Health, 2019)
Background: Diarrhoea has evident itself among the leading causes of under-five childhood mortality globally as well as in India. Although the benefits of zinc supplementation in diarrhoea management have been established, there remain many barriers to the widespread implementation of this treatment strategy. In India, a very small proportion of children in need, 20 per cent in urban and merely 5 per cent in rural, have access to zinc supplementation. The study aimed to assess zinc adherence in the community and find out the preferential mode of zinc as tablet or syrup, to stick to the scheduled adherence. Methods: The proposed method of study is a simple household survey complimented by secondary research around the preference and usage of zinc and ORS among under five children, suffered from diarrhoea in the last 14 days preceding the survey date. Results: The study revealed that 95 per cent of the respondents preferred zinc syrup over zinc tablet for treatment of diarrhoea due to its ease to administer and palatable taste to children. Eighty nine per cent of the total urban and 62 per cent of total rural respondents received zinc in syrup form, indicating the preferred mode of zinc by service providers over tablets. Conclusions: It has been observed that the caregivers tend to give the complete dosage of zinc if it is available in the syrup form. However, it is important to generate evidence to understand the preferential mode of zinc; tablet or syrup in terms of administration of drug, its usage and its cost.